(untitled) (European Journal of Formal Sciences and Engineering, 2019)
Indonesia is one of the largest coal producer countries in the world. In the previous research, it is stated that coal producer countries are able to affect economic growth. The purpose of the study is to investigate the co-integration and causal relationships between coal consumption and income in Indonesia for the period of 1965-2016 using Granger causality test based on Vector Error Correction Model (VECM) employing population as the control variable in bivariate system. The Augmented Dicky-Fuller (ADF) and Phillips-Perron (PP) tests were used to determine the variable stationarity. From Johansen’s co-integration tests, it is indicated that there is a long-run relationship between the variables. The empirical study shows that there is no causal relationship between coal consumption and economic growth in Indonesia since coal consumption in fact cannot affect economic growth in Indonesia. Export tax becomes government revenues earned from energy sectors including coal.